A replacement name for Dalodesmus sakalava (de Saussure & Zehntner, 1901) (Diplopoda: Polydesmida: Dalodesmidae) - Mesibov, Robert; Wesener, Thomas; Hollier, John (Zootaxa, 2018)
Polydesmus (Pterodesmus) voeltzkowi nom. nov. is proposed as a replacement name for Polydesmus (Pterodesmus) sakalava de Saussure & Zehntner, 1901, now Dalodesmus sakalava (de Saussure & Zehntner, 1901), a junior primary homonym of Polydesmus sakalava de Saussure & Zehntner, 1897.